(untitled) - Eagly, Alice Hendrickson (Boston, Mass., 2007)
This book's rich analysis is founded on scientific research from psychology, economics, sociology, political science, and management. The authors ground their conclusions in that research and invoke a wealth of engaging anecdotes and personal accounts to illustrate the practical principles that emerge. With excellent leadership in short supply, no group, organisation, or nation can afford to restrict women's access to leadership roles. This book evaluates whether such restrictions are present and, when they are, what we can do to eliminate them.
Keywords: Lãnh đạo nữ,Leadership in women